2001
DOI: 10.1111/1467-6451.00160
|View full text |Cite
|
Sign up to set email alerts
|

Internet Car Retailing

Abstract: We investigate the e¡ect of Internet car referral services on dealer pricing of automobiles in California. Customers of an online service pay on average 2% less for their car (6450 for the average car). 25% of the savings come from purchasing at low-price dealerships a¤liated with the online service. The remaining 75% stem from information provision by the online service, bargaining by the service on behalf of consumers, and cost e¤ciencies. A consumer receiving the mean online price does better than 65% of o¥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(39 citation statements)
references
References 12 publications
1
38
0
Order By: Relevance
“…(For example, see Brynjolfsson and Smith, 2000; Scott Morton, Zettelmeyer and Silva-Risso, 2001; Brown and Goolsbee, 2002; and Ellison and Ellison, 2009.) Hastings and Weinstein (2008), in a study of school choice where government plays a major role, found parents were more likely to choose a school with higher average test scores after receiving difficult to gather publicly available information about school scores.…”
Section: Introductionmentioning
confidence: 99%
“…(For example, see Brynjolfsson and Smith, 2000; Scott Morton, Zettelmeyer and Silva-Risso, 2001; Brown and Goolsbee, 2002; and Ellison and Ellison, 2009.) Hastings and Weinstein (2008), in a study of school choice where government plays a major role, found parents were more likely to choose a school with higher average test scores after receiving difficult to gather publicly available information about school scores.…”
Section: Introductionmentioning
confidence: 99%
“…This information can then be sold to automobile retailers as valuable sales leads, usually through a subscription model covering a specific geographic region (Chen, Iyer, and Padmanabhan 2002). Past research has suggested that customers purchasing through infomediaries obtain a discount when compared with offline customers (Morton, Zettelmeyer, and Silva-Risso 2001). In addition, Viswanathan et al (2007) found that the extent of the discount is dependent on the type of infomediary visited, with customers of price infomediaries paying the least and product infomediaries paying more.…”
Section: Infomediary Sales Channels In Automobile Retailingmentioning
confidence: 99%
“…The channel profit shown in Equation (2) is a simplification of the overall profit related to the use of the infomediary channel by the retailer. Sellers often discount prices in online channels (Morton, Zettelmeyer, and Silva-Risso 2001), and as a result, maximizing profitability involves incorporating an understanding of the degree to which new sales channels cannibalize sales in the existing channels (Geyskens, Gielens, and Dekimpe 2002). However, in a fluctuating sales environment in which the total lead-based sales are relatively low, sellers are likely to take a myopic view of management of the channel.…”
Section: Analytical Model Of Infomediary Sales Channelsmentioning
confidence: 99%
See 2 more Smart Citations